2010
DOI: 10.1515/epoly.2010.10.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of comonomer effect and hydrogen effect on internal donor in ethylene/1-hexene copolymerizations with MgCl2-supported catalysts

Abstract: Abstract:Ethylene homopolymerization and copolymerizations with 1-hexene by three types of MgCl 2 -supported catalysts were compared. Cat-1 contains no internal electron donor (ID), Cat-2 contains phthalic anhydride (PA) as ID, and Cat-3 contains anisole as ID. The influences of two kinds of ID on comonomer effect, the role of hydrogen, polymerization kinetics in ethylene/1-hexene copolymerization were investigated. The addition of ID improves the catalysts activities in ethylene polymerization. In comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
2
3
0
Order By: Relevance
“…This was because the addition of internal donor decreased sensitivity of catalyst activity to external donor. This result is in good agreement with that of Zhang et al [5]. They reported that the addition of phthalic anhydride or anisole as internal donor can depress the sensitivity of catalyst activity to hydrogen in ethylene /1-hexene copolymerization.…”
Section: Catalytic Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…This was because the addition of internal donor decreased sensitivity of catalyst activity to external donor. This result is in good agreement with that of Zhang et al [5]. They reported that the addition of phthalic anhydride or anisole as internal donor can depress the sensitivity of catalyst activity to hydrogen in ethylene /1-hexene copolymerization.…”
Section: Catalytic Activitysupporting
confidence: 93%
“…However, Zhang et al studied effect of hydrogen in ethylene/1-hexene copolymerization in the presence of internal donor. They found that hydrogen can improve the catalyst activity in ethylene/1-hexene copolymerization when it presents in a small concentration [5]. At this point, the effect of hydrogen is still unclear, but it is interesting to investigate further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was because the addition of internal donor decreased sensitivity of catalyst activity to hydrogen. This result is in good agreement with that of Zhang et al They reported that the addition of phthalic anhydride or anisole as internal donor can depress the sensitivity of catalyst activity to hydrogen in ethylene /1hexene copolymerization 127 . b Activity ratio without H2 = activity of the modified catalyst/activity of the unmodified catalyst c Activity ratio with H2 = activity of the catalyst at that level of H2/activity of that catalyst without H2…”
Section: Effect Of Alkoxysilanes On Catalytic Activitysupporting
confidence: 92%
“…[19][20][21] In the long-term research and development of supported Z-N catalysts for polyethylene production, the olefin polymerization kinetics, CCD of LLDPE, and morphology of the nascent polymer particles have been found to be effectively changed by introducing electron donors like esters, ethers, amides and alkoxysilanes in the catalysis system. [6][7][8]10,13,[22][23][24][25][26][27][28][29][30][31][32][33] Considering the importance of electron donors in supported Z-N catalysts, various research approaches have been adopted to disclose the mechanism of the electron donor effects, including spectroscopic analysis, [34][35][36][37][38][39][40] analysis on catalyst morphology, [41,42] and molecular simulation. [8,[43][44][45][46][47][48][49] Besides these approaches, mechanistic studies based on polymerization kinetics and counting of the active centers have also made important contributions to this topic.…”
Section: Introductionmentioning
confidence: 99%